Pesticides and the evolution of the genetic structure of Anopheles coluzzii populations in some localities in Benin (West Africa) - FASSINOU, Arsène Jacques Y. H.; KOUKPO, Come Z; Razaki, A. Ossè; Agossa, Fiacre R.; Azondékon, Roseric; Sominahouin, André; Kpanou, Casimir; Sagbohan, Hermann; Yovogan, Boulais; Akogbéto, Martin C.; SEZONLIN, MICHEL (My University, 2019)
Carbamates, pyrethroids, organophosphorus and organochlorines use have been reported in all localities except Sô-Ava. Anopheles coluzzii was strongly represented across all study localities. The L1014F allele was observed in the localities of Kétou, Cotonou and Zagnanado. Likewise, insecticide selection pressure of homozygous resistant individuals (L1014F/L1014F) was significantly higher in Kétou, Cotonou and Zagnanado (p value < 0.05). Surprisingly in Sô-Ava, a relatively high frequency of the L1014F allele despite the reported absence of pesticide use was observed. All mosquito populations were found to be deficient in heterozygosity across the study sites (FIS< 0). No genetic differentiation (FST< 0) was observed in the localities of Zagnanado and Kétou
Keywords: Anopheles coluzzii; Genetic structure; Pesticide; Malaria; Resistance; Benin